Comprehensive investigation on the reactivity of triarylphosphine radical cations by laser flash photolysis time‐resolved UV–Vis spectroscopy. (2nd May 2016) - Yasui, Shinro; Kobayashi, Shinjiro; Mishima, Masaaki
Abstract : Laser flashphotolysis at 266 nm was carried out on the acetonitrile solution of triarylphosphines, Ar3 P, using a Nd YAG laser under oxygen, air, and argon atmospheres by varying the Ar3 P concentration. The spectral change was monitored by time‐resolved UV–Vis spectroscopy. A transient absorption that appeared on the TRUV spectrum within 100 ns after the laser flash was judged to result from the triarylphosphine radical cation, Ar3 P +, based on a comparison with previously reported spectra. The absorption decayed on a time scale of microseconds according to the first‐order kinetics, in which the first‐order rate constant, k obs, is expressed by k obs  =  k O2 [O2 ] +  k Ar [Ar3 P] +  k s . The first term in this expression represents the radical coupling of Ar3 P + with O2, whereas the second term likely results from an ionic reaction of Ar3 P + with the parent phosphine. This finding suggests that Ar3 P + undergoes either a radical coupling with oxygen or an ionic reaction with Ar3 P to decay. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Laser flash photolysis time‐resolved UV–Vis spectroscopy was performed at 266 nm on an acetonitrile solution of triarylphosphines, Ar3 P, under various atmospheres by varying the concentration of Ar3 P. The triarylphosphine radical cation, Ar3 P +, which appeared within 100 ns after the laser flash, decayed on a time scale of microseconds according to the first‐order kinetics. Dependence of the first‐order rate constant on [O2 ] and [Ar3 P] suggests that Ar3 P + undergoes either a radical coupling with oxygen or an ionic reaction with Ar3 P.